2016
DOI: 10.1016/j.futures.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

New future perspectives through constructive conflict: Exploring the future of gas in the Netherlands

Abstract: This paper reports on the refinement of constructive conflict methodology (CCM) combining Q methodology and stakeholder dialogue workshops for gas futures for the Netherlands. Since the end of the 1950s, natural gas exploration and exploitation has been a major focus of the Dutch energy policy. Discussions about the future of energy in the Netherlands tend to focus either on pro-gas or pro-renewable energy. Using Q methodology we have constructed more nuanced perspectives on the future of energy in the Netherl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Emerging visions are usually rooted in entirely different beliefs, values and mental frameworks initially not shared by larger groups in society [13]. Such visions are typically associated with outsiders, who are likely to conduct rule-breaking behaviour [54,55], because they pursue divergent and sometimes marginal perspectives [56]. Learning is key to vision development and niche formation [13], but our focus is more on the interaction of visions and actors in niches and less on learning processes and knowledge.…”
Section: Agencymentioning
confidence: 99%
“…Emerging visions are usually rooted in entirely different beliefs, values and mental frameworks initially not shared by larger groups in society [13]. Such visions are typically associated with outsiders, who are likely to conduct rule-breaking behaviour [54,55], because they pursue divergent and sometimes marginal perspectives [56]. Learning is key to vision development and niche formation [13], but our focus is more on the interaction of visions and actors in niches and less on learning processes and knowledge.…”
Section: Agencymentioning
confidence: 99%
“…A detailed description of this model and the data used for quantification can be found in (Eker 2016). Ligtvoet et al (2016) have identified six perspectives that describe what several aspects of the Dutch energy system are expected to look like in the next fifty years according to the key stakeholders in the sector. They consider these perspectives as qualitative exploratory scenarios that describe visions on the future of the energy system.…”
Section: The Dutch Gas Sector and Six Stakeholder Perspectivesmentioning
confidence: 99%
“…More nuanced perspectives focusing on economic conditions or uncertainty have also been uncovered. A brief summary of these perspectives is presented in Table 1, while a more extended description of perspective narratives can be found in (Ligtvoet et al 2016).…”
Section: The Dutch Gas Sector and Six Stakeholder Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations